Profit Growth: Redefining Success with an Advanced ROA Model - Arwani, Agus; Masrur , Muhamad; Muhammad , Rifqi (Owner : Riset dan Jurnal Akuntansi, 2024)
This study explores the influence of Return on Assets (ROA) on profit growth in the food and beverage industry subsector listed on the Indonesia Stock Exchange Sectoral Index (ISSI). Employing a quantitative research approach, financial data from 11 companies, selected purposively for the period 2019-2023, were subjected to regression analysis. ROA serves as a key financial performance indicator, reflecting a company's effectiveness in utilizing its assets to generate profit, whereas profit growth serves as a crucial marker of business sustainability. The results indicate a significant positive correlation between ROA and profit growth, suggesting that firms with higher ROA tend to exhibit superior profit growth compared to those with lower ROA. This highlights the critical role of efficient asset utilization in bolstering business performance and sustainability. The study offers practical insights for companies in the food and beverage sector, emphasizing the importance of strategies aimed at optimizing asset management to achieve enhanced profit growth. Furthermore, the research adds to the existing body of literature by providing a detailed analysis of the ROA-profit growth relationship within the Indonesian market. Future studies could broaden the scope by increasing the sample size and including companies from various sectors and regions to confirm and expand upon these findings.